Obese Male Mice Exposed to Early Life Stress Display Sympathetic Activation and Hypertension Independent of Circulating Angiotensin II - Carolina Dalmasso; Nermin S. Ahmed; Sundus Ghuneim; Cole Cincinelli; Jaqueline R. Leachman; Jorge F. Giani; Lisa Cassis; Analia S. Loria (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background We have previously reported that male mice exposed to maternal separation and early weaning (MSEW), a model of early life stress, show sympathetic activation and increased blood pressure in response to a chronic high‐fat diet. The goal of this study was to investigate the contribution of the renin–angiotensin–aldosterone system to the mechanism by which MSEW increases blood pressure and vasomotor sympathetic tone in obese male mice. Methods and Results Mice were exposed to MSEW during postnatal life. Undisturbed litters served as controls. At weaning, both control and MSEW offspring were placed on a low‐fat diet or a high‐fat diet for 20 weeks. Angiotensin peptides in serum were similar in control and MSEW mice regardless of the diet. However, a high‐fat diet induced a similar increase in angiotensinogen levels in serum, renal cortex, liver, and fat in both control and MSEW mice. No evidence of renin–angiotensin system activation was found in adipose tissue and renal cortex. After chronic treatment with enalapril (2.5 mg/kg per day, drinking water, 7 days), an angiotensin‐converting enzyme inhibitor that does not cross the blood–brain barrier, induced a similar reduction in blood pressure in both groups, while the vasomotor sympathetic tone remained increased in obese MSEW mice. In addition, acute boluses of angiotensin II (1, 10, 50 μg/kg s.c.) exerted a similar pressor response in MSEW and control mice before and after enalapril treatment. Conclusions Overall, elevated blood pressure and vasomotor sympathetic tone remained exacerbated in MSEW mice compared with controls after the peripheral inhibition of angiotensin‐converting enzyme, suggesting a mechanism independent of angiotensin II.